Lansia Sehat Bebas Hipertensi di Kelurahan Kenali Asam Bawah Kota Jambi - Maimaznah Maimaznah; Tina Yuli Fatmawati (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2020)
Hypertension or high blood pressure is a condition when a person experiences an increase in blood pressure either slowly or suddenly (acutely). Although the increase in blood pressure is relatively small, this can reduce life expectancy. In the United States, one in three adults suffers from hypertension, which generally does not cause complaints, even though it has been experienced for years. Target and output: The community, especially the Elderly in Kelurahan Kenali Asam Bawah, aims to increase the elderly's knowledge about the management and prevention of hypertension. This activity was carried out in the month. The implementation method included discussion and question and answer about problems related to the prevention of hypertension, giving meida education, blood pressure checking, monitoring and evaluation. Results: After the health education of the elderly understood about hypertension and out of 15 elderly people who were present, 6 elderly people were found to have blood pressure above normal (> 140/90 mmHg). To the elderly who experience high blood pressure is expected to always continue to do blood pressure checks. It is expected that the community, especially RT 11 of the Kenali Asam Bawah village to maintain a healthy lifestyle